Induction of Bradyrhizobium japonicum common nod genes by isoflavones isolated from Glycine max - Kosslak, Renee M. (1987)
The early events in legume nodulation by Rhizobium spp. involve a conserved gene cluster known as the common nod region. A broad-host-range plasmid (pEA2-21) containing a Bradyrhizobium japonicum nodDABC-lacZ translational fusion was constructed and used to monitor nod gene expression in response to soybean root extract. Two inducing compounds were isolated and identified. Analysis using ultraviolet absorption spectra, proton nuclear magnetic resonance, and mass spectrometry showed that the two inducers were 4′,7-dihydroxyisoflavone (daidzein) and 4′,5,7-trihydroxyisoflavone (genistein). Induction was also seen with some, but not all, of the flavonoid compounds that induce nod genes in fast-growing Rhizobium strains that nodulate clover, alfalfa, or peas. When pEA2-21 was introduced into Rhizobium trifolii, it was inducible by flavones but not by daidzein and genistein. In Rhizobium fredii, pEA2-21 was induced by isoflavones and flavones. Thus, the specificity of induction appears to be influenced by the host-strain genome.